Antimicrobial activity of medicinal plants against some pathogenic microbial strains - Charu Arora Chugh,; Dipti Bharti,; Suman Gupta, (International Journal of Phytomedicine, 2013)
Methanol extracts of ten plant species have been screened for their antimicrobial potential against fungal pathogens namely Aspergillus niger and Candida albicans and bacterial strains Escherichia coli and Bacillus subtilis. Extracts of all the plant species taken for the present study except Cucumis anguri showed fungicidal activity against both the fungal pathogens used. Leaves extract of Withania somniferaexhibited maximum 80-95% inhibition against both of the fungal pathogens, while extract of Azadirachta indica showed 88% growth inhibition against C. albicans. Acacia nilotica and Withania somnifera have shown inhibition zones of 17 and 19mm respectively against E. coli and B. subtilis. All the plant species have shown significant antibacterial potential in the range of 1-18mm against B. subtilis. Azadirachta indica, Cucumis anguri, Emblica officinalis and Solanum nigrum did not exhibit any antibacterial activity against E. coli. The identification of these potential herbs as antimicrobial agents will be helpful in replacing some commercially synthesized antimicrobial drugs.